PROBLEM-BASED LEARNING ASSISTED BY INTEGRATED LEARNING MEDIA BASED ON SOCIAL MEDIA TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS - Hariyanto, Hariyanto; Nasruliyah Hikmatul , Maghfiroh (Journal of Education Technology and Inovation, 2024)
SMAN 1 Besuki organizes education and learning that leads to 21st century skills. One of the 21st century skills developed is students' critical thinking skills. The critical thinking skills of class XI MIPA 1 students in the 2024/2025 Academic Year, especially in biology learning based on the results of interviews with biology subject teachers, still need to be improved, this is confirmed by the results of students' critical thinking ability tests with an average of 49.85 with a category still underdeveloped. The purpose of this study was to determine the role of Blended Problem Based Learning with integrated social media-based learning media in improving the critical thinking skills of class XI MIPA 1 students. This study is a Classroom Action Research based on Lesson Study. Data on critical thinking skills were obtained using a critical thinking test with essay-type questions. Data from students' critical thinking skills tests were analyzed descriptively qualitatively by referring to the Illinois Critical Thinking Essay Test. The results show that the results of students' critical thinking tests in cycle I and cycle II increased by 9.83%, which means that the critical thinking skills of class XI MIPA 1 students in the 2024/2025 Academic Year have developed well in biology learning using Blended-Problem Based Learning with integrated social media-based learning media.